Metabolic regulation of dendritic cell activation and immune function during inflammation - Wu, Lili; Yan, Ziqi; Jiang, Yiyang; Chen, Yingyi; Du, Juan; Guo, Lijia; Xu, Junji; Luo, Zhenhua; Liu, Yi (Frontiers in Immunology, 2023)
Dendritic cells (DCs) are antigen-presenting cells that bridge innate and adaptive immune responses. Multiple cell types, including DCs, rely on cellular metabolism to determine their fate. DCs substantially alter cellular metabolic pathways during activation, such as oxidative phosphorylation, glycolysis, fatty acid and amino acid metabolism, which have crucial implications for their functionality. In this review, we summarize and discuss recent progress in DC metabolic studies, focusing on how metabolic reprogramming influences DC activation and functionality and the potential metabolic differences among DC subsets. Improving the understanding of the relationship between DC biology and metabolic regulation may provide promising therapeutic targets for immune-mediated inflammatory diseases.